2023
DOI: 10.36941/ajis-2023-0008
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Perceptions of Grocery Retail Managers on Private Label Brands in South Africa

Abstract: The phenomenon of private label brands has been widely studied from various contexts, with South Africa as no exception. The pervading economic climate across the globe, as a consequence of the Covid 19 pandemic, has brought the study of private label brands to the fore. Private label brands (PLBs) are considered a cheaper alternative with comparable levels of quality to manufacturer products, which creates a value proposition for consumers (Cuneo et al., 2019). Notwithstanding the plethora of research in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Customers' perceptions of private label products are complex and encompass a number of factors, such as overall satisfaction, trust, and dependability. Prominent private labels effectively regulate consumer perception by means of open and honest communication, favorable feedback, and reliable product delivery [13], [31]- [34]. Hypothesis 5: There is a positive relationship between consumer perception and private label success.…”
Section: Consumer Perceptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Customers' perceptions of private label products are complex and encompass a number of factors, such as overall satisfaction, trust, and dependability. Prominent private labels effectively regulate consumer perception by means of open and honest communication, favorable feedback, and reliable product delivery [13], [31]- [34]. Hypothesis 5: There is a positive relationship between consumer perception and private label success.…”
Section: Consumer Perceptionmentioning
confidence: 99%
“…Studies have indicated that consumers are drawn to private brands due to their ability to reduce costs without sacrificing quality [16]. Price-wise, private label products that are strategically positioned have been associated with higher market share and greater customer loyalty [13]. Hypothesis 1: There is a positive relationship between pricing strategy and private label success.…”
Section: Pricing Competitivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, [46] found that consumers are still largely familiar with national brands as opposed to private label brands. As a result, [47] encourage grocery retailers in the future to subside their investments on private label brand awareness. In future, to counter this misfortune, grocery retailers can explore the following brand awareness enhancement avenues.…”
Section: Prospects In Private Label Brand Awarenessmentioning
confidence: 99%